Flame-retardant hydrophilic superoleophobic composite membrane as well as preparation method and application thereof

By depositing graphene oxide composite materials on the surface of the flame-retardant microporous base film, a flame-retardant hydrophilic super oleophobic composite film was prepared, which solved the problem of low separation efficiency and poor pollution resistance of oil-water separation membranes in the prior art. The problem of not having flame retardancy has achieved efficient oil-water separation and excellent flame retardant performance.

CN119425414APending Publication Date: 2025-02-14CHANGZHOU UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411600359.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing oil-water separation membrane has low separation efficiency, poor pollution resistance and no flame retardancy, making it difficult to effectively deal with oil-water mixtures with fire risk.

Method used

A flame-retardant hydrophilic superoleophobic composite film was prepared by depositing graphene oxide (GO) and mica composite materials on the surface of the flame-retardant microporous base film. The graphene oxide sheet diameter of the film material is 0.2-5 μm, the average particle diameter of mica is 200 mesh, the mass ratio is 200-1000:1, and the membrane pore diameter is 0.02-1.2 μm.

Benefits of technology

The flame-retardant hydrophilic superoleophobic composite membrane exhibits high water flux and high oil retention, has excellent anti-pollution and self-cleaning properties, and has good flame retardancy and research potential in the field of oil-water separation for offshore fires. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to the technical field of oil-water separation, in particular to a flame-retardant hydrophilic superoleophobic composite membrane as well as a preparation method and application thereof, and particularly aims at oil-water separation of diesel oil. A commercial organic nylon film which is low in cost and easy to obtain is adopted as a substrate, one-step modification is performed through a mixed solution of graphene oxide and muscovite, and then a vacuum suction filtration method is performed. The composite membrane provided by the invention has high separation efficiency and high flux, and more importantly, the composite membrane prepared by the invention also has excellent flame retardant ability and good self-cleaning ability. The method is simple in steps, easy to control and very low in requirements on production equipment, so that the oil-water separation flame-retardant membrane has obvious industrial application prospects and research potential in the field of solving offshore oil spill fire accidents.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of oil-water separation, and in particular relates to a flame-retardant hydrophilic super-oleophobic composite membrane and a preparation method and application thereof. Background Art

[0002] As the global industrialization continues to increase, the large amount of oily wastewater generated by industrial production and human activities is accelerating the destruction of only 1% of the available freshwater resources on the earth. Oil spills and the discharge of industrial oily wastewater pollutants have seriously affected water quality, brought many toxic compounds to the oceans and lakes, and threatened various species in biological systems and even humans. Therefore, the treatment of oily wastewater has become one of the most urgent environmental problems to be solved by countries around the world.

[0003] According to the oil droplet size (d, μm) of oily wastewater and its existence in water, oily wastewater is usually divided into four categories: floating oil (d>100), dispersed liquid (10≤d≤100), emulsified oil (0.1≤d<10), and dissolved oil (<0.1). Traditional separation technologies such as flotation, centrifugation, ultrasonic separation, coagulation, biological treatment, etc. have many disadvantages such as complex system design, low separation efficiency, high operating cost, and generation of secondary pollutants. Membrane separation, as an advanced purification technology, selects membrane materials with selective permeability, uses the concentration difference on both sides of the separation membrane or its own selective permeability to separate target pollutants, thereby completing the separation and extraction of different components. Compared with traditional separation processes, it has the advantages of economic efficiency, energy saving, and easy operation. Microfiltration membranes and ultrafiltration membranes are mainly used to separate dispersed oil and emulsified oil with a particle size of less than 100 µm in oily wastewater. The surface of hydrophobic and oleophilic membranes is easily contaminated by oil, while hydrophilic and oleophobic membranes retain oil and allow water to pass through. It is a purely physical separation process that is highly efficient and energy-saving and has been widely used in the field of oil-water separation research.

[0004] For environments with fire risks, such as offshore oil spills, or petrochemical refineries and oilfield wastewater, higher requirements are placed on the flame retardancy of separation membranes. Surface modification and blending modification of membranes are commonly used research methods, but in the current preparation of separation membranes, some polymer membrane materials are difficult and expensive to prepare, or cause environmental pollution during the preparation process. Therefore, the research focus of oil-water separation membranes is on the environmental friendliness of separation membrane materials, high efficiency and stability during use, and low cost of processing and production.

[0005] Chinese patent CN107724080A obtains super hydrophobic flame retardant fabric with oil-water separation function by modifying the fabric with fluorine-containing polymers with epoxy groups and silicon-containing compounds with amino groups. Hui Li et al. (BioRes. 2019, 14 (4), 9298-9306) achieved super hydrophobicity and flame retardancy by forming magnesium hydroxide nanostructures on the surface of filter paper and then treating it with polydimethylsiloxane (PDMS). Shifeng Zhang et al. (J. Environ, 2022, 10 (3), 107580) prepared a super hydrophobic, flame retardant and magnetic polyurethane sponge for oil-water separation by adding flame retardant phytic acid and dip coating with Fe3O4 nanoparticles and graphene oxide. The above technical solutions have problems such as complex preparation methods, easy contamination of membrane materials, low mechanical strength, or low separation efficiency. Summary of the invention

[0006] In view of the problems in the prior art that conventional microfiltration or ultrafiltration membranes have low separation efficiency, poor anti-pollution performance and lack of flame retardancy, the purpose of the present invention is to provide a flame retardant hydrophilic superoleophobic composite membrane and a preparation method and application thereof.

[0007] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows: A first aspect of the present invention provides a flame-retardant hydrophilic and super-oleophobic composite membrane, which is obtained by depositing a composite material of graphene oxide (GO) and muscovite mica on the surface of a flame-retardant microporous base membrane.

[0008] Furthermore, the thickness of the graphene oxide and muscovite composite material on the surface of the flame-retardant microporous base membrane is 2.4-2.8 μm.

[0009] Furthermore, the graphene oxide sheet has a diameter of 0.2-5 μm.

[0010] Furthermore, the average particle size of the muscovite is 200 meshes.

[0011] Furthermore, the mass ratio of the muscovite to the graphene oxide is 200-1000:1.

[0012] Furthermore, the flame-retardant microporous base membrane is selected from any one of an organic nylon filter membrane, a polyvinylidene fluoride filter membrane, and a polyethersulfone filter membrane.

[0013] Furthermore, the pore size of the flame retardant microporous base membrane is 0.02-1.2 μm; preferably, the pore size of the membrane is 0.20-0.22 μm.

[0014] A second aspect of the present invention provides a method for preparing the above-mentioned flame retardant hydrophilic super oleophobic composite film, comprising the following steps: (1) dispersing graphene oxide in deionized water to obtain a GO dispersion with a mass concentration of 20-25 μg / mL; (2) uniformly dispersing muscovite, deionized water and GO dispersion by ultrasonic dispersion to obtain a GO-modified muscovite deposition liquid; the mass concentration of GO in the GO-modified muscovite deposition liquid is 0.4-0.5 μg / mL; (3) The GO-modified muscovite in the deposition liquid is deposited onto the surface of the flame-retardant microporous base membrane by vacuum filtration and then naturally dried at room temperature.

[0015] The third aspect of the present invention provides the use of the flame-retardant hydrophilic and super-oleophobic composite membrane in oil-water separation.

[0016] Specifically, the flame retardant hydrophilic superoleophobic composite membrane is used in separating diesel emulsion.

[0017] The present invention has the following beneficial effects: (1) The flame-retardant hydrophilic and superoleophobic composite membrane obtained by the present invention has high water flux and high oil retention capacity, and has good oil-water separation ability for diesel emulsion; (2) The flame-retardant hydrophilic and super-oleophobic composite film obtained by the present invention has excellent anti-pollution and self-cleaning properties; (3) The method for obtaining a hydrophilic and super-oleophobic composite membrane of the present invention is simple, the raw materials are cheap, the reaction conditions are not harsh, and it is green and pollution-free, effectively avoiding the impact of the modifier on the environment; (4) The flame-retardant hydrophilic and super-oleophobic composite membrane obtained in the present invention has excellent flame retardancy and has good research potential and application prospects in the field of oil-water separation in marine fires. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 These are TG and DTG characterization test graphs of the composite films and muscovite mica powder obtained in Examples 1, 3, and 5.

[0019] Figure 2 These are the combustion test images of Yun-5 and Nylon films obtained in Example 5 at different times.

[0020] Figure 3 These are scanning electron microscope images of Nylon membrane, GO membrane, and Yun-4 at different magnifications.

[0021] Figure 4 The water flux, diesel permeation flux and rejection rate, underwater dichloromethane contact angle, and optical microscope images before and after diesel filtration of Yun-1, Yun-2, Yun-3, Yun-4, and Yun-5 membranes obtained in Examples 1-5 (the left side is before filtration, and the right side is after filtration).

[0022] Figure 5These are the underwater oleophobic performance test (methylene chloride oil droplets after dyeing) and anti-pollution performance test images (n-hexane solution after dyeing) of the Yun-5 membrane obtained in Example 5. DETAILED DESCRIPTION

[0023] The present invention is described in detail below with reference to the examples. However, it should be understood that the following examples are only illustrative of the embodiments of the present invention, and are not intended to limit the scope of the present invention.

[0024] The raw materials used in the following specific examples are as follows: Graphene oxide was obtained by Hummer's method and purchased from Shenzhen Suiheng Technology Co., Ltd. (Shenzhen, China) with the product number SH-GO-1266. The sheet diameter was 0.2-5 μm and the thickness was 1 nm.

[0025] Muscovite powder, with an average particle size of 200 mesh, was purchased from Guzhang County Shanlin Shiyu Mineral Products Co., Ltd. (Hunan, China) with the product number MU220706.

[0026] The microporous base membrane is a Nylon 66 organic nylon membrane with a thickness of 0.08 mm, a diameter of 50 mm, and a pore size of 0.22 μm. It was purchased from Haining Delv New Material Technology Co., Ltd. (Zhejiang, China) with the item number DL-NY50022.

[0027] Other raw materials or reagents not specifically specified in the present invention are commonly available on the market.

[0028] It should be noted that the preparation method of the GO dispersion in the following specific examples is as follows: graphene oxide powder is dispersed in deionized water to obtain a GO dispersion with a mass concentration of 20 μg / mL, and the dispersion is sealed and stored at low temperature for later use. Example 1

[0029] A method for preparing a flame-retardant hydrophilic and super-oleophobic composite film comprises the following steps: (1) Ultrasonic dispersion of 4 mg of muscovite powder, 49 mL of deionized water and 1 mL of GO dispersion was uniformly performed to obtain GO-modified muscovite deposition liquid; (2) GO-modified muscovite was deposited onto the surface of the microporous base membrane by vacuum filtration and then naturally dried at room temperature. The obtained composite membrane was named Yun-1. Example 2

[0030] A method for preparing a flame-retardant hydrophilic and super-oleophobic composite film comprises the following steps: (1) Ultrasonic dispersion of 8 mg of muscovite powder, 49 mL of deionized water and 1 mL of GO dispersion was uniformly performed to obtain GO-modified muscovite deposition liquid; (2) GO-modified muscovite was deposited onto the surface of the microporous base membrane by vacuum filtration and then naturally dried at room temperature. The obtained composite membrane was named Yun-2. Example 3

[0031] A method for preparing a flame-retardant hydrophilic and super-oleophobic composite film comprises the following steps: (1) Ultrasonic dispersion of 12 mg of muscovite powder, 49 mL of deionized water and 1 mL of GO dispersion was uniformly performed to obtain GO-modified muscovite deposition liquid; (2) GO-modified muscovite was deposited onto the surface of the microporous base membrane by vacuum filtration and then naturally dried at room temperature. The obtained composite membrane was named Yun-3. Example 4

[0032] A method for preparing a flame-retardant hydrophilic and super-oleophobic composite film comprises the following steps: (1) Ultrasonic dispersion of 16 mg of muscovite powder, 49 mL of deionized water and 1 mL of GO dispersion was uniformly performed to obtain GO-modified muscovite deposition liquid; (2) GO-modified muscovite was deposited onto the surface of the microporous base membrane by vacuum filtration and then naturally dried at room temperature. The obtained composite membrane was named Yun-4. Example 5

[0033] A method for preparing a flame-retardant hydrophilic and super-oleophobic composite film comprises the following steps: (1) Ultrasonic dispersion of 20 mg of muscovite powder, 49 mL of deionized water and 1 mL of GO dispersion was uniformly performed to obtain GO-modified muscovite deposition liquid; (2) GO-modified muscovite was deposited onto the surface of the microporous base membrane by vacuum filtration and then naturally dried at room temperature. The obtained composite membrane was named Yun-5. Example 6

[0034] A method for preparing a flame-retardant hydrophilic and super-oleophobic composite film comprises the following steps: (1) Ultrasonic dispersion of 24 mg of muscovite powder, 49 mL of deionized water and 1 mL of GO dispersion was uniformly performed to obtain GO-modified muscovite deposition liquid; (2) GO-modified muscovite was deposited onto the surface of the microporous base membrane by vacuum filtration and naturally dried at room temperature. Powder fell off and the obtained composite membrane was named Yun-6. Example 7

[0035] A method for preparing a flame-retardant hydrophilic and super-oleophobic composite film comprises the following steps: (1) Ultrasonic dispersion of 28 mg of muscovite powder, 49 mL of deionized water and 1 mL of GO dispersion was uniformly performed to obtain GO-modified muscovite deposition liquid; (2) GO-modified muscovite was deposited onto the surface of the microporous base membrane by vacuum filtration and naturally dried at room temperature. Powder fell off and the obtained composite membrane was named Yun-7. Example 8

[0036] A method for preparing a mica composite film comprises the following steps: (1) Ultrasonic dispersion of 20 mg of muscovite powder and 50 mL of deionized water was performed to obtain a muscovite deposition liquid; (2) The muscovite mica was deposited onto the surface of the microporous base membrane by vacuum filtration and then dried naturally at room temperature. The obtained composite membrane was named Yun-8. Example 9

[0037] A method for preparing a graphene oxide composite film comprises the following steps: (1) Ultrasonic dispersion of 49 mL of deionized water and 1 mL of GO dispersion was uniformly dispersed to obtain GO deposition solution; (2) GO was deposited onto the surface of the microporous base membrane by vacuum filtration and dried naturally at room temperature. The obtained composite membrane was named GO membrane.

[0038] The indirect ignition method was used to observe whether the film would self-extinguish. The TG characterization and limiting oxygen index test were used to analyze the improvement of its thermal performance and to examine the flame retardancy of the composite film. The results are shown in Figure 1 and Table 1.

[0039] Table 1 Flame retardancy test results of composite films .

[0040] As can be seen from Table 1, when the muscovite content is below 20 mg, the limiting oxygen index increases with the increase of the muscovite content, and when the muscovite content is 24 mg and 28 mg, the oxygen index is still 25%. This indicates that when the muscovite content reaches 20 mg, it is the maximum content value that the composite film can withstand under normal use, and the maximum oxygen index value of the composite film of this formula is 25%.

[0041] Figure 1The TG and DTG characterization test diagrams of Yun-1, Yun-3, Yun-5 composite membranes and muscovite powder. It can be seen from the analysis of the TG and DTG test characterization diagrams that during the entire calcination process, muscovite almost had no mass loss, and it showed extremely excellent thermal stability. Therefore, the mass loss of all composite molds can be attributed to the substrate. After the composite membrane was modified with muscovite, its resistance to high temperature was improved. The mass loss of all composite membranes under temperature conditions below 350°C was almost negligible, which also showed that the GO@Ms composite membrane prepared in this paper had good thermal stability below this temperature. With the increase of muscovite content, its overall weight loss rate and weight loss rate are gradually decreasing, which shows that the addition of muscovite greatly improves the high temperature resistance of the composite membrane.

[0042] Figure 2 It is the combustion test image of Yun-5 obtained in Example 5 and the Nylon film without surface modification. It can be seen from the figure that the Nylon film began to ignite the moment it came into contact with the flame, and then the flame was removed and the film burned directly into ashes. However, the unmodified area of ​​the modified composite film prepared by the present invention was instantly ignited when it just came into contact with the flame, and then the fire source was removed, and it was found that the flame self-extinguished when it spread to the modified area. The modified area was then ignited, and it was found that the composite film was not directly ignited, but showed extremely strong flame resistance. The composite film was ignited when the fire source continued to burn for 3s, but the substrate did not burn directly, and the muscovite protective layer was burned, and then the thin film structure of the substrate was left ( Figure 2 (the red circled part in d1).

[0043] Composite membrane related performance test: Due to the overload phenomenon of Yun-6 and Yun-7 composite membranes, the composite membranes showed powder shedding and were extremely unstable when not in use, and had lost their practical significance and potential, so no oil-water separation test was performed on them. Only the composite membranes obtained in Examples 1-5 of the present invention were tested for related performances, and the test results are shown in Table 2.

[0044] Among them, the test method is as follows: (1) Water contact angle: The contact angle formed between a water droplet and the membrane surface is tested using the angle measurement method. When the contact angle is less than 90°, it is described as hydrophilic. When the contact angle is close to 0° or is 0°, it is described as super hydrophilic.

[0045] (2) Underwater oil contact angle: The contact angle formed between the underwater oil droplet and the membrane surface is tested using the angle measurement method. When the contact angle is greater than 90°, it is described as oleophobic, and when the contact angle exceeds 150°, it is described as superoleophobic.

[0046] (3) Water flux test method: Use a vacuum filtration device (vacuum pump pressure 0.08 MPa) to measure the water flux J of the membrane at the speed at which 100 mL of pure water passes through the composite membrane. The specific formula is:

[0047] Where, J: water flux, unit is L∙m -2 ∙h -1 , V: filtrate volume (L), A: effective membrane permeation area (m 2 ), Δ t: filtration time (h) (4) Test method for oil permeation flux and oil retention rate: The oil permeation flux K of the membrane is determined by the speed at which 100 mL of water-in-oil emulsion passes through the composite membrane using a vacuum filtration device (vacuum pump pressure 0.08 MPa). The specific formula is: , where K is the oil permeation flux, in L∙m -2 ∙h -1 , V: filtrate volume (L), A: effective membrane permeation area (m 2 ), Δ t filtration time (h).

[0048] Oil retention rate R: Use a TOC tester to measure the oil concentration of the solution before and after separation. The specific formula is: ; where C i (mg / L) and C0 (mg / L) are the oil concentrations of the filtered and original oil-in-water emulsions, respectively, in mg / L.

[0049] The preparation method of the oil-in-water emulsion is as follows: To simulate the real situation, 5 g of seawater salt (Xingcheng Dingxinsheng Trade Mall, Liaoning, China) was weighed and dissolved in 99 mL of deionized water to prepare simulated seawater. 99 mL of prepared seawater and 1 mg of sodium dodecyl sulfate (as an emulsifier) ​​were added to the container, and then 1 mL of diesel oil was put into the container with 99 mL of deionized water, and ultrasonic stirring was performed for 30 min, and then magnetic stirring was performed for 5 min to obtain a stable emulsion.

[0050] Table 2 Composite membrane performance test results .

[0051] Figure 3 The scanning electron microscope images of organic nylon membrane, GO membrane and Yun-4 at different magnifications. It can be seen from the image that graphene oxide is evenly dispersed on the nylon fibrous structure, muscovite has the characteristics of lamellar stacking, completely covering the basement membrane and graphene oxide particles are intercalated on the lamellar mica, and the originally smooth surface of nylon becomes rough, indicating that the surface of the nylon membrane has been successfully modified.

[0052] Figure 4(a) is the oil permeation flux and retention rate of the composite membrane; Figure 4 (b) is the water flux of the composite membrane; Figure 4 (c) is the underwater dichloromethane contact angle of the composite film; Figure 4 (d) Optical microscope image of Yun-5 before and after diesel filtration (left side is before filtration, right side is after filtration).

[0053] Drop Sudan III (Shanghai Bidex) dyed dichloromethane on the surface of Yun-5 membrane. Figure 5 The process of placing, immersing and taking out the Yun-5 membrane in the Sudan III-stained n-hexane solution is shown in (a1-a5). Figure 5 As shown in (b1-b5), it can be seen that the Yun-5 membrane is not stained, indicating that the filter membrane prepared by the present invention has excellent anti-pollution performance.

[0054] Through multiple test analyses, it was concluded that the Yun-5 membrane obtained in Example 5 had the best performance.

[0055] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A flame retardant hydrophilic super oleophobic composite film, characterized in that: It is obtained by depositing graphene oxide and muscovite composite materials on the surface of flame retardant microporous base membrane.

2. The flame-retardant hydrophilic and super-oleophobic composite film according to claim 1, characterized in that: The thickness of the graphene oxide and muscovite composite material on the surface of the flame-retardant microporous base membrane is 2.4-2.8 μm.

3. The flame-retardant hydrophilic and super-oleophobic composite film according to claim 1, characterized in that: The flake diameter of the graphene oxide is 0.2-5 μm; the average particle size of the muscovite is 200 meshes.

4. The flame-retardant hydrophilic and super-oleophobic composite film according to claim 1, characterized in that: The mass ratio of the muscovite to the graphene oxide is 200-1000:

1.

5. The flame-retardant hydrophilic and super-oleophobic composite film according to claim 1, characterized in that: The flame-retardant microporous base membrane is selected from any one of an organic nylon filter membrane, a polyvinylidene fluoride filter membrane, and a polyethersulfone filter membrane.

6. The flame-retardant hydrophilic and super-oleophobic composite film according to claim 1, characterized in that: The pore size of the flame retardant microporous base membrane is 0.02-1.2 μm.

7. The method for preparing the flame-retardant hydrophilic and super-oleophobic composite film according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) dispersing graphene oxide in deionized water to obtain a GO dispersion with a mass concentration of 20-25 μg / mL; (2) Ultrasonic dispersion of muscovite, deionized water and GO dispersion to obtain GO-modified muscovite deposition liquid; (3) The GO-modified muscovite in the deposition liquid is deposited onto the surface of the flame-retardant microporous base membrane by vacuum filtration and then naturally dried at room temperature.

8. The method for preparing the flame-retardant hydrophilic and super-oleophobic composite film according to claim 7, characterized in that: The mass concentration of GO in the GO-modified muscovite deposition solution is 0.4-0.5 μg / mL.

9. Use of the flame-retardant hydrophilic and super-oleophobic composite membrane according to any one of claims 1 to 6 in oil-water separation.

10. The use of the flame-retardant hydrophilic and super-oleophobic composite film according to claim 9, characterized in that: Application of the flame-retardant hydrophilic and super-oleophobic composite membrane in separation of diesel emulsion.

Citation Information

Patent Citations

  • Super-hydrophobic flame retardant fabric with function of separating oil from water and preparation method thereof

    CN107724080A

  • Nanocellulose / two-dimensional material composite flame-resistant material and preparation method thereof

    CN105754146A

  • Preparation method of high temperature-resistant super-hydrophilic filter element

    CN108815884A

  • Two-dimensional layered response film and preparation method and application thereof

    CN114291822A

  • Flame-retardant super-hydrophilic oleophobic composite membrane for oil-water separation and preparation method of flame-retardant super-hydrophilic oleophobic composite membrane

    CN118341268A